Beta diversity response to stress severity and heterogeneity in sensitive versus tolerant stream diatoms. Issue 3 (11th December 2018) - Pound, Katrina L.; Lawrence, Gregory B.; Passy, Sophia I.
Abstract: Aim: Severity and heterogeneity of stress are major constraints of beta diversity, but their relative influence is poorly understood. Here, we addressed this question by examining the patterns of beta diversity in stress‐sensitive versus stress‐tolerant stream diatoms and their response to local versus regional factors along gradients of stress severity and heterogeneity. Location: The Adirondack region of New York. Methods: Beta diversity was measured as multivariate dispersion of communities across high stress, low stress, and high + low stress (heterogeneous) environments, encompassing 200 stream samples. Null models were implemented to assess community similarity relative to randomly assembled communities and the importance of local assembly processes versus the regional species pool. Results: The overall beta diversity was influenced by a combination of severity and heterogeneity of stress, while beta diversity of sensitive species increased with heterogeneity. Beta diversity of tolerant species did not vary with either severity or heterogeneity of stress. Heterogeneity decreased community similarity relative to the null expectation in all groups of species. Stress reduced the importance of local assembly mechanisms for the overall beta diversity and sensitive species beta diversity. In contrast, the importance of local assembly mechanisms increased with stress regarding beta diversity of tolerant species. Main conclusions: Beta diversity responded to both severity and heterogeneity of stress, but turnover along these gradients was mostly driven by sensitive species. The overall beta diversity and beta diversity of sensitive species became more constrained by the depauperate regional species pool, as opposed to local assembly mechanisms. While heterogeneous stress contributed to beta diversity, severe stress suppressed beta diversity through elimination of sensitive species. Therefore, an increase in beta diversity in an environmentally‐stressed region may serve as a forewarning for future loss of sensitive species, should the stress continue to intensify.